Metta Analisis Pengaruh Model Pembelajaran Inquiry pada Mata Pelajaran IPS - Eka Gaetri Utari; Melisyah Kurnia Wati; Primadi Khema Chandra; Rina Setiani; Gustina Masitoh (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study aims to evaluate the effectiveness of the inquiry learning model in improving learning activities and student learning outcomes in the classroom using the Classroom Action Research (PTK) method, data were collected from two cycles conducted in the same class. The results showed a significant increase in teacher and student activities, with the average teacher activity increasing from 62.49% to 87.49% and student activity from 60.46% to 85.04%. In addition, the average student learning outcomes also increased from 68.47 to 83.94. Nonetheless, the study identified challenges such as students' different abilities and limited resources that need to be addressed for successful implementation. The findings confirm the importance of innovation in learning methods to improve the quality of education and the need for continuous support from all relevant parties.